Asuhan Keperawatan Gerontik Pada Pasien Dengan Hipertensi Di Panti Sosial Tresna Werdha Sabai Nan Aluih Sicincin Kabupaten Padang Pariaman - Allisya Naswadiya Putri; Ramaita .; Armaita .; Hasmita . (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Hypertension is a chronic disease characterized by an increase in blood pressure ≥140/90 mmHg and commonly occurs in the elderly. Hypertension can cause serious complications such as stroke, heart failure, and kidney failure if not properly managed. This study aimed to provide gerontic nursing care for hypertensive patients at the Sabai Nan Aluih Sicincin Social Nursing Home, Padang Pariaman Regency. The method used was a case study with a nursing process approach conducted on one hypertensive patient from February 26  to March 3, 2026. The assessment results showed that the patient experienced chronic pain, ineffective health management, and risk of falls. Nursing interventions included pain management using deep breathing relaxation techniques, progressive muscle exercises, blood pressure monitoring, health education, a low-salt diet, and fall risk prevention. Nursing evaluation showed an increase in the patient’s knowledge regarding hypertension and the importance of adherence to treatment. After five days of nursing interventions, there was a decrease in pain intensity, improved therapy adherence, and improvement in the patient’s general condition. The recommendations given were to maintain a healthy lifestyle, improve medication adherence, and routinely monitor blood pressure. The conclusion of this study showed that the implementation of comprehensive and systematic gerontic nursing care was highly effective in overcoming nursing problems in hypertensive patients.